BOʻLAJAK TARBIYAChILARNING KOGNITIV QOBILIYATLARINI RIVOJLANTIRISh METODIKASINING OʻZIGA XOS JIHATLARI - Bazarbaeva, A.K. (SCIENCE and SOCIETY, 2025)
The article states that in the development of cognitive abilities of future educators, their spiritual and moral development is important. Cognitive development is closely linked to moral and spiritual qualities. This includes the use by educators of pedagogical approaches based on mutual respect and emotional intuition to ensure the moral development of students. Feature: in the development of cognitive abilities of educators, their ability to solve moral problems also plays an important role. This supports the spiritual achievements of the pupils in work.
Keywords: cognitive; abilities; healthy generation; cognitive development; thinking; logic; semiotics; multimedia technologies; interactive whiteboard; electronic textbooks; digital platforms; facilitator